Processo comunicacional familiar no contexto do câncer infantil - Borges, Amanda Aparecida (2013)
Childhood cancer is a chronic disease of permanent and long lasting. It is a condition considered rare, when compared to adults, representing 0.5% to 3% of malignant tumors. When it affects the household, their routine undergoes significant changes, either by hospitalization or treatment process. In the redimensioning the family to meet the needs of child care, family members still encounter the difficult task of establishing communication with the child about his disease, requiring the reflection and support facility to cope with the disease. This manner, the present study aimed to know how to the family communicates with the child about cancer. This is a qualitative study, directed by symbolic interactionism as theoretical reference and thematic content analysis as a methodological reference. The data were collected through semi-structure interviews with families of children with cancer, who were in treatment for at least three months in a health care institution in the state of Minas Gerais. The analysis of data emerged from dynamically interconnected themes and categories, which concluded that family to establish communication with the child about his disease adopts a protectionist language. The disease stigma associated with informational support that the family receives health professionals and members of the family, makes the child's family choose words to give meaning to change in routine. This manner, the family, to dialogue with the child, no pervades the severity of the disease. The interaction that occurs in the subsystem and system family provides an extra subsidy that directly interferes with the meanings attributed by families and affect their actions. Even without exposing the disease severity , the family does not fail to show for the child the need to perform treatment for their rehabilitation, makes it so that the child collaborate during the procedures. The family believes that the transmission of messages of overcoming and optimism helps the child to overcome the disease.